Crystal structure of 3-methoxybenzyl 2-(6-methoxynaphthalen-2-yl)propanoate, C22H22O4 - Sun Quan-Le; Lin Da-Zhuan; Xue De-Dong; Lin Ying (Zeitschrift für Kristallographie - New Crystal Structures)
C22H22O4, orthorhombic, P212121 (no. 19), a = 5.861(2) Å, b = 8.140(2) Å, c = 37.654(8) Å, V = 1796.4(8) Å3, Z = 4, R gt(F) = 0.0310, wR ref(F 2) = 0.0812, T = 100(2) K.